Population Characteristics of Shirdi Tourism Place : A Geographical Analysis - Gadekar Deepak Janardhan (International Journal of Scientific Research in Science and Technology, 2025)
This research paper relies on secondary data and the said data is taken from Indian Census. The main objective is to study the population characteristics of Shirdi tourist center. Although natural, social, economic and political factors affect population growth, tourism is one factor. Because Shirdi is an international tourist center and because of this tourist center many businesses have been created in this area and many people are engaged in various businesses. Due to this, various people are attracted here and the population is increasing here. Therefore, it is important to study the demographic characteristics of Shirdi tourist center from this perspective the said study has been done.
Keywords: Population Characteristics; Sex Ratio; Population Density; Growth Rate; Literacy